2022
DOI: 10.3390/cells11060964
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Expression of TIGIT, PD-1, TIM-3, and CD39 by γδ T Cells in Ovarian Cancer

Abstract: Phenotypic characterization of γδ T cells in the MALs (malignant ascites lymphocytes), TILs (tumor infiltrating lymphocytes), and PBLs (peripheral blood lymphocytes) of ovarian cancer (OvCA) patients is lacking. Therefore, we quantified γδ T cell prevalence in MAL, TIL, and PBL specimens from n = 18 OvCA patients and PBL from age-matched healthy donors (HD, n = 14). Multicolor flow cytometry was performed to evaluate the expression of inhibitory receptors (TIGIT, PD-1 and TIM-3), stimulatory receptors (Ox40), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…TIGIT and PD-1 high co-expression was observed in PBLs (peripheral blood lymphocytes), MALs (malignant ascites lymphocytes), and TILs with increased frequency in tumor proximity in matched samples of patients at first diagnosis of ovarian cancer not treated ( 129 ). Moreover, the authors also observed TIGIT and TIM3 co-expression in PBLs, MALs, and TILs but with a decreased frequency in tumor proximity ( 129 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…TIGIT and PD-1 high co-expression was observed in PBLs (peripheral blood lymphocytes), MALs (malignant ascites lymphocytes), and TILs with increased frequency in tumor proximity in matched samples of patients at first diagnosis of ovarian cancer not treated ( 129 ). Moreover, the authors also observed TIGIT and TIM3 co-expression in PBLs, MALs, and TILs but with a decreased frequency in tumor proximity ( 129 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…In their paper, Weimer et al focus on the phenotypic characterization of γδ, Vδ1 and Vδ2 T cells in ovarian cancer. On all γδ, Vδ1 and Vδ2 T cells in PBLs, MALs and TILs from OC patients, they compared the expression levels of several co-regulatory receptors (CRRs), such as PD-1, TIM-3, Ox40, TIGIT (T cell immunoreceptor with Ig and ITIM domains), and two ectoenzymes CD39 and CD73 [ 28 ]. Previous findings have pointed out that PD-1 coexpression with TIM-3 or LAG-3 on T cells in patients with solid tumors is associated with immune exhaustion [ 28 , 29 ].…”
Section: Tim-3mentioning
confidence: 99%
“…On all γδ, Vδ1 and Vδ2 T cells in PBLs, MALs and TILs from OC patients, they compared the expression levels of several co-regulatory receptors (CRRs), such as PD-1, TIM-3, Ox40, TIGIT (T cell immunoreceptor with Ig and ITIM domains), and two ectoenzymes CD39 and CD73 [ 28 ]. Previous findings have pointed out that PD-1 coexpression with TIM-3 or LAG-3 on T cells in patients with solid tumors is associated with immune exhaustion [ 28 , 29 ]. In their study, they demonstrated for the first time the expression of these checkpoints on phenotypically different Vδ1 cells in OC.…”
Section: Tim-3mentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral terminally differentiated Vδ2 T cells of breast cancer patients were demonstrated to display exhaustion phenotype with elevated PD‐1 expression, which was significantly associated with tumor‐draining lymph node invasion 42 . Recently, coexpression of PD‐1, Tim‐3, CD39 with TIGIT was reported on tumor‐infiltrating Vδ1 T cells in ovarian cancer, implying an increased state of exhaustion 43 . A majority of tumor‐infiltrating Vγ9 ‐ γδ T cells were detected in both lymphomas and solid tumors, which is quantitatively correlated with tissue residency and exhaustion and response to immune checkpoint therapy 44 .…”
Section: Activated γδ T Cells Exhibit Exhaustion Signaturementioning
confidence: 99%